The promise and pain of devising as deliberative democracy: Out Of Character Theatre Company's Fresh Visions trilogy. Issue 3 (3rd July 2022) - Heinemeyer, Catherine; Birch, Paul; Rowe, Nick
ABSTRACT: Out Of Character Theatre Company's Fresh Visions project pursued an innovative theatre-based research methodology which enabled sustained, in-depth, polyphonic and dialogic engagement around the future shape of local mental health services. Since our previous research (Heinemeyer, Catherine and Nick Rowe. 2019. 'Being Known, Branching Out: Troupes, Teams and Recovery.' Mental Health Review Journal 24(3): 212-227) indicated that theatre devising can act as 'intuitive democracy', we ask whether Fresh Visions constituted a deliberative democracy exercise. We explore both the 'promise' of theatre-led approaches to overcome power imbalances and embrace dissent in deliberative processes, and their attendant 'pain' and limitations.